2016
DOI: 10.1186/s40405-016-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Gambling among adolescents with and without hearing loss

Abstract: ObjectivesThis exploratory study investigates the prevalence of gambling, preferred types of gambling, and problem gambling in Swedish young people aged 15–18 years with and without hearing loss.MethodsA cross-sectional health survey was conducted in Örebro County, Sweden in 2014. A standardized questionnaire was distributed to 4888 students, and 4329 filled it. There were 318 (8 %) students with hearing loss. The response rate was 82 %. The 2-item Lie/Bet questionnaire (Johnson et al. in Psychol Rep 80:83–88,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…At present, there are more opportunities for adolescents to start and carry on gambling due to the quick-change nature of the digital technologies, where new types of games, technologies to access them, and gambling providers have proliferated fast [22]. In spite of gambling is an age-restricted activity in most of the countries, several authors found that this activity (online) is relatively common in adolescents and is also increasingly recognized as a major public health problem [22][23][24], although in a percentage less common than the land-based variant [25][26][27][28]. Regarding prevalence, the current research has found that it varies between 0.2% and 12.3% in adolescents, showing values of 2.5-5.6% of adolescents who meet risk gambling criteria [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are more opportunities for adolescents to start and carry on gambling due to the quick-change nature of the digital technologies, where new types of games, technologies to access them, and gambling providers have proliferated fast [22]. In spite of gambling is an age-restricted activity in most of the countries, several authors found that this activity (online) is relatively common in adolescents and is also increasingly recognized as a major public health problem [22][23][24], although in a percentage less common than the land-based variant [25][26][27][28]. Regarding prevalence, the current research has found that it varies between 0.2% and 12.3% in adolescents, showing values of 2.5-5.6% of adolescents who meet risk gambling criteria [29][30][31].…”
Section: Introductionmentioning
confidence: 99%